Memoria Passionis dalam Perayaan Ekaristi sebagai Dasar Pengembangan Teologi Migrasi - Monteiro, Yohanes Hans; Jew, Jean Loustar; NaE, Roberthus Gaga (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2025)
Abstract. The unfair treatment experienced by migrants in overseas lands should receive a response from the Church by grounding migration theology. This article was written to provide a theological basis for the development of migration theology so that it can encourage the formation of a synodal Church for migrants. By using literature research methods, this article confirms that the idea on memoria passionis can function as a theological foundation for the development of migration theology and the realization of the Church's synodality with migrants. The form of Church synodality with migrants that we offer in this article is the Church's openness to listen to and learn from the life experiences of migrants, the development of collaborative work of the Church with related parties in order to fight for the noble dignity of migrants, and the implementation of pastoral diakonia in the form of animation, mediation, and advocacy.Abstrak. Perlakuan tidak adil yang dialami oleh kaum migran di tanah rantau sudah sepatutnya mendapat respons dari Gereja dengan membumikan teologi migrasi. Artikel ini ditulis untuk memberikan pendasaran teologis bagi pengembangan teologi migrasi sehingga dapat mendorong pembentukan Gereja yang sinodal untuk kaum migran. Dengan menggunakan metode studi pustaka, artikel ini menegaskan bahwa gagasan memoria passionis dapat berfungsi sebagai salah satu landasan teologis untuk pengembangan teologi migrasi dan perwujudan sinodalitas Gereja bersama kaum migran. Bentuk sinodalitas Gereja bersama kaum migran yang kami tawarkan dalam artikel ini ialah keterbukaan diri Gereja untuk mendengarkan dan belajar dari pengalaman hidup kaum migran, pengembangan kerja kolaboratif Gereja bersama pihak-pihak terkait dalam rangka memperjuangkan martabat luhur kaum migran, dan pelaksanaan pastoral diakonia dalam bentuk animasi, mediasi, dan advokasi.